Contextualizing English Textbooks: Harnessing Sabang’s Cultural and Natural Potentials - Cut Mulia Zuhra; Sabrina Sabrina (Universitas Teuku Umar, 2026)
The integration of local culture and natural potential into English learning materials has gained attention in recent years, particularly as educators seek more contextually relevant resources. While English textbooks in Indonesia often rely a foreign content, there is a notable gap in materials that reflect students’ immediate environment and cultural identity. Responding to this need, the present study focuses on developing an English textbook that incorporates the natural potential and local culture of Sabang Island, making language learning more meaningful and relatable for secondary school students.This study applied a Research and Development (R&D) methodology, which involved the following stages: (1) needs analysis, (2) data collection, (3) textbook design, (4) expert validation, (5) revision, (6) field testing, and (7) final product. The data were gathered through expert validation sheets, student questionnaires, and classroom observations. The research subjects included 20 eighth-grade students from SMPN 8 in Sabang Island. Classroom observation indicated that most English textbooks used general content in nature. As a result, students often struggle to relate the material to their real-life experiences, since the content tends to feel unfamiliar or removed from their daily lives. Validation results from content and design experts indicated that the textbook is highly suitable in terms of content relevance, language appropriateness, and layout aspects. receiving validation scores of 96%, 92.72%, and 91.66% respectively. In addition, student feedback showed strong enthusiasm for the textbook, suggesting that integrating local culture and natural context into English learning significantly boosts engagement and comprehension.